Reactions and COVID-19 disease progression following SARS-CoV-2 monoclonal antibody infusion - Laurel Goldin (Elsevier, 2021)
SARS-CoV-2 monoclonal antibodies (mAbs) have been proposed as a treatment for mild to moderate COVID-19, with favorable outcomes reported in clinical trials and an emergency use authorization granted by the Food and Drug Administration. Real-world data remain limited, however, and thus this analysis presents findings from over 6,500 outpatient administrations of mAb at facilities affiliated with a large healthcare organization in the United States. Within 48 hours of mAb infusion, 15.6% (1,043) of patients received a drug that was indicative of a possible reaction to the infusion; the majority of these were mild (e.g., acetaminophen). Approximately 5.2% of patients who received mAb (n=347) had a post-infusion emergency department visit or admission for COVID-19 disease progression. The results of this analysis indicate that patients who receive mAb have a low likelihood of both an immediate negative reaction to the treatment as well as future inpatient admission related to COVID-19 disease progression.